REKAYASA BIOPLASTIK UNTUK KEMASAN MAKANAN DARI KHITOSAN LIMBAH KULIT UDANG DAN PATI TAPIOKA, DENGAN MINYAK KELAPA SAWIT SEBAGAI PEMLASTIS - Muhammad Hasan (Department of Environmental Engineering-Faculty of Civil, Environmental and Geo Engineering. Institut Teknologi Sepuluh Nopember, Surabaya, 2010)
Synthesis of biodegradable polymers is an alternative technology, which can be applied to cope with the problem of petrochemical raw materials packaging waste buildup. The purpose of this study was to obtain information on the effect of chitosan composition, tapioca starch and palm oil as plasticizer on mechanical and thermal properties, crystallinity, and oxygen permeability. Bioplastics was synthesis by blending tapioca starch, chitosan, and palm oil at various compositions. The results showed that bioplastic could be synthesized and printed in the form of film. Bioplastic films showed a low permeability, where the more content of chitosan in a mixture of bioplastics caused the lower permeability to oxygen. Tensile strength of the resulting film was low and the optimum value was achieved on chitosan/starch compoxition of 60/40. Elongation at the film break was strongly influenced by starch composition. High starch composition produced bioplastics with high elasticity. The melting point range was 133-150 °C. Films with the highest value of this parameter were produced from samples with tapioca starch/chitosan ratio of 60/40. Thermal resistance of the sample was determined by tapioca starch/chitosan ratio of 50/50, with weight loss of 41.395% at 475 oC. Almost all films produced in various compositions of chitosan/tapioca starch showed amorphous structure, except sample with tapioca starch/chitosan ratio of 10/90, which was semicrystalline.